The Management of the Endowed Property in the Case of Not Appointing and Not Choosing the Administrator (Arabic: مُتوَلِّی) of Endowment by the Founder (Arabic: واقِف, Wāqif) - Majid Ostad Moadab Khoshrou; Golam Reza Yazdani; Mustafa Hosseini (آموزه‌‌های فقه مدني)
The way to manage waqf (Arabic: وَقْف, endowment) is one of the main issues in the endowment contract. The responsibility of the management of the endowed property rests with the administrator (Arabic: مُتوَلِّی) according to the opinion of jurists and also the civil law. The administrator is usually appointed by the founder (Arabic: واقِف, Wāqif) during the endowment. Now, the question arises who will be the administrator, if the founder has not appointed the administrator? Article 81 of the amendment of the Civil Code has identified the custodian as the ruler in public endowments, which does not have a specific custodian. According to Clause 1 of Article 1 of the Law on Institutions and Powers of the Organization of Hajj and Endowments and Charitable Activities (Affairs), approved on December 23, 1984, the administration of general endowments that do not have an administrator or have unknown administrators and if the expedient of the endowment and the next generation or resolving the dispute of beneficiaries of an endowment (Arabic: مَوْقُوفٌ ‌عَلَیْهِم) are subjected to the intervention of the guardian of the Islamic jurist in private endowment (endowment for the benefit of certain individuals) will be delegated to this organization from the date of approval of this law. However, the opinions of jurists differ where the founder does not appoint an administrator in the endowment. Some believe that the administration (trusteeship) is with the beneficiaries of an endowment in both types of endowments. A group considers the administration as the ruler in every kind of it. Some believe that the administrator in the general endowment is the ruler and the beneficiaries of an endowment bear the mentioned responsibility in the private endowment. It was concluded, by analytical-descriptive method and using the library method, in this study that the administrator of the endowed property is the ruler in cases where the founder does not specify the administrator in the endowment, and there is no difference between the general endowment and the private endowment in this regard.